PEMODELAN INDEKS PEMBANGUNAN MANUSIA PROVINSI JAWA BARAT, JAWA TIMUR DAN JAWA TENGAH TAHUN 2019 DENGAN MENGGUNAKAN METODE REGRESI LOGISTIK ORDINAL - Meylita Sari; Purhadi Purhadi (Jurnal Gaussian, 2021)
Ordinal logistic regression is one of the statistical methods to analyze response variables (dependents) that have an ordinal scale consisting of three or more categories. Predictor variables (independent) that can be included in the model are category or continuous data consisting of two or more  variables. Human Development Index (HDI) is an indicator of the success of human development in a region and can be categorized into medium, high and very high. Based on the further categorization, in this study would like to know more about the HDI model using the Ordinal Logistic Regression method, with predictor variables that are suspected to affect, so that it is obtained in West Java Province is influenced by variable poverty rates and clean water sources with a classification accuracy value of 77.78%, Central Java Province is influenced by variable economic growth rate based on constant price GDP, poverty rate and open unemployment rate with a classification accuracy value of 82.85%. East Java province is influenced by variable poverty rate and open unemployment rate with a classification accuracy value of 76.31%. As well as in the three provinces in Java Island is influenced by variable economic growth rate, variable poverty rate, variable clean water source with a classification accuracy value of 73%.